Decoding Spatial Versus Non-spatial Processing in Auditory Working Memory - Erhart, Mira; Czoschke, Stefan; Fischer, Cora; Bledowski, Christoph; Kaiser, Jochen (Frontiers in Neuroscience, 2021)
Objective: Research on visual working memory has shown that individual stimulus features are processed both in specialized sensory regions and higher cortical areas. Much less evidence exists for auditory working memory. Here a main distinction has been proposed between the processing of spatial and non-spatial sound features. Our aim was to examine feature-specific activation patterns in auditory working memory. Methods: We collected fMRI data while 28 healthy adults performed an auditory delayed match-to-sample task. Stimuli were abstract sounds characterized by both spatial and non-spatial information, i.e., interaural time delay and central frequency, respectively. In separate recording blocks, subjects had to memorize either the spatial or non-spatial feature which had to be compared with a probe sound presented after a short delay. We performed both univariate and multivariate comparisons between spatial and non-spatial task blocks. Results: Processing of spatial sound features elicited higher activity in a small cluster in superior parietal lobe than sound pattern processing, whereas there was no significant activation difference for the opposite contrast. Multivariate analysis was applied using a whole-brain searchlight approach to identify feature-selective processing. The task-relevant auditory feature could be decoded from multiple brain regions including auditory cortex, posterior temporal cortex, middle occipital gyrus, and extended parietal and frontal regions. Conclusions: In summary, the lack of large univariate activation differences between spatial versus non-spatial processing could be attributable to the identical stimulation in both tasks. In contrast, whole-brain multivariate analysis identified feature-specific activation patterns in widespread cortical regions. This suggests that areas beyond the auditory dorsal and ventral streams contribute to working memory processing of auditory stimulus features.